Immediate Outcomes of Aortic Valve Neocuspidization with Glutaraldehyde-treated Autologous Pericardium: a Multicenter Study - Arutyunyan,Vagram (2020)
Abstract Objective: To determine the feasibility of aortic valve neocuspidization (AVNeo) with glutaraldehyde-treated autologous pericardium. Methods: One hundred and seventy (170) AVNeo (84 males/86 females) were performed from January 2017 through March 2019 in three centers. All the records were prospectively collected and retrospectively reviewed. Results: Most of the patients were older than 60 years and over 95% were operated for aortic stenosis. Preoperatively, pressure gradients were 69.9±21.3 mmHg for patients with aortic stenosis, and the surgical annular diameter was 21.0±2.0 mm for all patients. Effective orifice area (EOA) and indexed EOA (iEOA) averaged 0.7±0.3 cm2 and 0.4±0.2 cm2/m2 for patients with aortic stenosis before surgery, respectively. There was no conversion to prosthetic aortic valve replacement. Eight patients needed reoperation for bleeding, but no patient needed reoperation due to early infective endocarditis. There were five in-hospital deaths due to noncardiac cause. Compared to preoperative echocardiographic measurements, postoperative peak pressure gradient decreased significantly (-58.7±1.7 mmHg; P<0.001) and reached 11.2±5.6 mmHg, and mean pressure gradient also decreased significantly (-36.8±1.1 mmHg; P<0.001) and reached 6.0±3.5 mmHg. Accordingly, EOA and iEOA increased significantly 2.0 cm2 and 1.0 cm2/m2 (both P<0.001) to reach 2.7±0.6 cm2 and 1.4±0.3 cm2/m2 after surgery, respectively, with minimal significant aortic regurgitation (0.6% > mild). Conclusion: AVNeo is feasible and reproducible with good clinical results. Hemodynamically, AVNeo produces immediate postoperative low-pressure gradients, large EOA, and minimal regurgitation of the aortic valve. Further studies are necessary to evaluate mid- and long-term evolution.